Long-term follow-up of an attenuated presentation of NAXE-related disease, a potentially actionable neurometabolic disease: a case report - Almudhry, Montaha; Prasad, Chitra; Rupar, C. Anthony; Tay, Keng Yeow; Prasad, Asuri N. (Frontiers in Neurology, 2024)
Background Early-onset progressive encephalopathy with brain edema and/or leukoencephalopathy (PEBEL-1) is an autosomal recessive disorder whereby a fluctuating clinical course is exacerbated by febrile illnesses. Pathogenic NAD(P)HX epimerase (NAXE) gene mutations underpin this disorder. This mutation damages the metabolite repair system involved in regenerating crucial redox carriers. Longer survival has rarely been reported in this potentially actionable entity. Objectives This case study aims to report a milder phenotype of a patient with NAXE gene mutation and his longitudinal follow-up of more than 20 years. Case report A 24-year-old man first became symptomatic in infancy with frequent initial neurological decompensations in the setting of infections with subsequent clinical improvement followed by stability with residual cerebellar dysfunction. Clinical features noted over the years include chronic ataxia, nystagmus, ptosis, mild spasticity of lower limbs, and neuropsychiatric symptoms. Cerebellar and spinal cord atrophy were noted in cranial and spinal MR imaging. Biallelic homozygous variants in the NAXE gene (c.733 A>C) were identified on whole exome sequencing. Symptom management included the initiation of a mitochondrial cocktail with carnitine, coenzyme Q, and thiamine. Subsequently, niacin (Vitamin B3), which is involved in the cellular biosynthesis of NAD+, was added, given its potentially beneficial therapeutic impact. Conclusion A missense homozygous variant in the NAXE gene is described in this patient with a milder clinical phenotype of the disease. Supplementation with niacin in addition to a mitochondrial cocktail presents a potential supportive therapeutic option to reduce disease progression.